Bathyconchoeciinae, a new subfamily of deep oceanic planktonic halocyprid Ostracod (Myodocopa, Ostracoda) - Angel, Martin; Graves, Carol (Zootaxa, 2013)
Species of the genera Bathyconchoecia and Scottoecia are currently classified in the subfamily Euconchoeciinae together with species of the genus Euconchoecia. The morphological and ecological characteristics of many of the species currently attributable to these two taxa are compared with a range of Euconchoecia species and are shown to differ extensively. These differences are sufficient to separate these taxa at the subfamily level. Therefore, a new subfamily, the Bathyconchoeciinae is proposed to accommodate all the species currently classified in the genera Bathyconchoecia and Scottoecia.